Emotional Intelligence, Self-Esteem and Academic Achievement: A Case Study, English Department Students - Wiwik Andreani (Humaniora, 2012)
This study examines the comparison between English Department students’ emotional intelligence (EQ), their self-esteem and their academic achievement. Twenty-two students participated in the research by answering EQ test and two Self-Esteem questionnaires. The result shows that there is no relation between students’ GPA and their self-esteem and EQ. This means that academic ability does not correspond to social skills. Though most students have average EQ and self-esteem, one student has High EQ, High Self-esteem and a 2.95 GPA (out of 4).